2013
DOI: 10.5935/1809-2667.20130002
|View full text |Cite
|
Sign up to set email alerts
|

Painéis MDF produzidos com resina poliuretana à base de óleo de mamona

Abstract: Este trabalho objetivou avaliar a viabilidade da produção de painéis MDF fabricados com madeiras das espécies Pinus caribaea e Eucalyptus grandis e resinas poliuretanas mono e bicomponente derivadas do óleo de mamona, com base nas recomendações da norma europeia Euro MDF Board (EMB/IS-2:1995). Os painéis desenvolvidos com ambas as resinas foram confeccionados com parâmetros de fabricação distintos, em razão de testes preliminares desenvolvidos. Com exceção da absorção de água após 24 horas dos materiais fabric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
1
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 7 publications
1
1
0
2
Order By: Relevance
“…The literature provides a wide range of MOE and MOR averages for similar studies evolving fiberboards. 5,7,44,48 These studies demonstrate that both the MOE as the MOR are characteristics that can suffer expressive alterations in its values, when another material is incorporated to the panels, as the observed in this research.…”
Section: Panels Characterizationsupporting
confidence: 70%
See 1 more Smart Citation
“…The literature provides a wide range of MOE and MOR averages for similar studies evolving fiberboards. 5,7,44,48 These studies demonstrate that both the MOE as the MOR are characteristics that can suffer expressive alterations in its values, when another material is incorporated to the panels, as the observed in this research.…”
Section: Panels Characterizationsupporting
confidence: 70%
“…Different studies demonstrate that the TS may vary widely, because it may be influenced by some factors as raw materials, kind of resin and the use or not of a hydrophobic agent. 7,34,43,44 Also, it is observed that there is a proportional relation between CR (Table 3) and TS, where the panels which presented the higher values of CR also were the ones that presented higher TS. This behavior can be attributed to a higher densification of these panels, which decrease empty spaces in the panel.…”
Section: Panels Characterizationmentioning
confidence: 80%
“…Valores semelhantes foram obtidos por Fiorelli, Bueno, e Cabral (2019), que avaliaram o compósito de resina poliuretano de mamona reforçado com fibras de côco verde, bagaço de cana-de-açúcar e obtiveram painéis com densidade de 530 kg/m³. Silva et al, (2013) avaliou a produção de painéis confeccionados com fibras de madeira Pinus e de Eucalyptus e resinas poliuretanas derivadas de óleo de mamona, obteve uma densidade de 500 kg/m³. Bertolini et al, (2014) produziu painéis provenientes de pinus sp.…”
Section: Ensaios Físicosunclassified
“…Os resultados de inchamento (Tabela 2) dos materiais compósitos, observa-se que o compósito de maior fibra na concentração de resina de 10% obteve maior inchamento com valor de 8,72 %, atendendo aos requisitos especificados de acordo com a NBR 14810-2:2018, onde preconiza um valor máximo de 22%. Silva et al, (2013) obteve um inchamento de 11,32%. Já Fiorelli, Bueno, e Cabral (2019) alcançou um inchamento com valor de 13,83%.…”
Section: Ensaios Físicosunclassified
“…Studies concerning the technological potential of alternative species for wood, with rapid growth and for multiple uses, are of great importance [1][2][3][4][5][6] in order to increase the supply of raw material in the construction sector and to minimize environmental pressures on native forests. Bamboo is a material that adapts to any type of soil (even where they are worn), requires few nutrients and its higher yields are obtained in areas where sugarcane is grown.…”
Section: Introductionmentioning
confidence: 99%